An agenda for mathematics education in the decade of education for sustainable development - Yasukawa, Keiko (NOMAD Nordic Studies in Mathematics Education, 2007)
The United Nations declared 2005 to 2014 as the Decade of education for sustainable development. This presents an opportune moment for mathematics educators and mathematics education researchers to reflect about the effectiveness that mathematics education has had in creating citizens for a sustainable future. There is an important distinction between education about sustainable development, and education for sustainable development; the latter is the more important, but also the more difficult and challenging. The paper examines some of the obstacles that mathematics educators face in educating for sustainable development, and identifies the need for some radical alternatives. These alternatives will need to challenge the dominant discourses that shape identities of both learners and teachers.